Mechanistic individualism versus organistic totalitarianism - Venter, J. J. (Koers, 1997)
Mechanistic individualism versus organistic totalitarianismIn this article it is argued that the organistic world picture, when functioning as a world view, is associated with a totalitarian view of social relationships, usually promoting the interests o f the state or the ethnic group as the interests which should dominate. This is illustrated by referring to the social ideas of Hobbes, Rousseau, D.H. Lawrence and Mussolini. The mechanistic world picture, however, when functioning as a world view, is associated with individualism, according to which the individuals have a relatively independent existence; it suggests that justice and morality are the automatic products of the equilibrating process. Cases in point: Hobbes, Adam Smith, Kant, Darwin, New-Classical and Monetarist economics. Finally (in Neo-Calvinist vein) it is argued that the application o f such worldviewish metaphors should be limited, so that justice can be done to both the differentiation of social relationships and their integration.